A risk‐based inventory of invasive plant species of Queensland, Australia: Regional, ecological and floristic insights. (23rd July 2019) - Osunkoya, Olusegun O.; Froese, Jens G.; Nicol, Sam; Perrett, Christine; Moore, Kerri; Callander, Jason; Campbell, Shane
Abstract: Invasive alien plant species threaten agriculture and biodiversity globally and require ongoing management to minimise impacts. However, the large number of invasive species means that a risk‐based approach to prioritisation is needed, taking into account the spatial scale of management decisions and myriad of available information. Here, we developed a risk‐based inventory of invasive plants in Queensland, Australia, using both current species distribution/abundance and the severity of their impacts. Our assessment followed a comprehensive data collection process including a scoping of local government pest management plans, herbarium records, the published literature and structured elicitation of expert knowledge during a series of regional stakeholder workshops. From 300 plant species that were identified as established and/or emerging invaders in the State, only one‐third were considered by practitioners to pose significant risks across regions to be considered management priorities. We aggregated regional species lists into a statewide priority list and analysed the data set (107 species) for historical, geographical, floristic and ecological patterns. Regions on the mainland eastern seaboard of the State share similar invasive plant communities, suggesting that these regions may form a single management unit, unlike the western/inland and the extreme far north (Torres Strait Islands) regions, which share fewer invasive plant species. Positive correlations were detected between invasiveness and time since introduction for some but not all plant life forms. Stakeholders identified research and management priorities for the invasive plant list, including biological control options, public awareness/education, effective herbicide use, ecology/taxonomy and risk analysis. In the course of the exercise, a statewide invasive plant priority list of high‐, medium‐ and low‐impact scores for policy, research and management was compiled. Finally, our approach to invasive plant species prioritisation highlighted that planning and policy documents are not necessarily reflected at the grass‐root level in terms of species identity and management priorities.